Efektivitas Terapi Latihan Pada Pasien Osteoarthritis - Rizkya Pratami; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Knee osteoarthritis (OA) is a pathological condition that attacks the joints, causing pain, immobility, and decreased quality of life. Physical exercise is one intervention that can be used. This review reviews and compares various types of exercise, such as strength training, aerobic, gradual programs, controlled weight training, and their impact on pain, knee function, and quality of life in knee OA patients. This study analyzed several Randomized Controlled Trial (RCT) studies that evaluated the effects of structured exercise in knee OA patients. Each study is 6 to 12 weeks long, with follow-up evaluations up to 1 year. Data were compared based on study design, type of intervention, measurement tools (such as WOMAC, KOOS, SF-36), and primary clinical outcomes. All studies show that physical exercise can significantly reduce pain, improve muscle strength, joint function and quality of life. Regular and structured exercise has been proven to be effective, safe, and worthy of being used as the main intervention in the management of knee OA. A digital, incremental approach can be a modern solution that increases patient engagement and success.